Perbandingan Penggunaan Data Hujan Satelit Dan Data Hujan Lapangan Untuk Pemodelan Hidrologi Hujan-Aliran (Studi Kasus DAS Tapung Kiri) - Linggasari, Rahma Setya; Sutikno, Sigit; Handayani, Yohanna Lilis (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Data availability for hidrologic modeling usually become a problem because of incompleteness and imprecision data. The development of advanced technology recently encourage the development of hydrological modeling by using remote sensing data. This research conducted rainfall-runoff modeling using remote sensing data and ground rainfall data with Integrated Flood Analysis System (IFAS) tools and took a case study in Tapung Kiri sub-watershed in Riau Province. This model was simulated and calibrated with rainfall-runoff periode of forward verification (2005-2006) and backward verification (2006-2005). The results of this research shows that the model to be optimal after calibration process in rain satellite data backward verification period from 1 January to 31 December 2005 by corellation value (R) 0.75, volume error (VE) of 3.22%, and coefficient of efficiency (CE) 0.9. It means that this model has a high degree of association with measurement data (0,7 < R < 1,0), the difference of volume can be tolerated ( VE < 5%), and effiency of this modeling with measurement discharge is highly efficient (CE > 0,75).Key words : rainfall-runoff modeling, satellite data, ground rainfall data, IFAS Model